Geographic perspectives of time poverty and the attainment of Sustainable Development Goal one in cities - Afolabi Olabamiji; Olayinka Ajala (Discover Cities)
Abstract Eradicating poverty in all its forms is one of the targets of the Sustainable Development Goals (SDGs), as it has been majorly defined by the international poverty line. Neglecting time poverty may deter the achieving the target of total eradication of poverty. Thus, this study assesses time poverty with the view of revealing the danger of focusing on only income poverty without considering time poverty in cities. The study adopted a grid sampling technique to select seven hundred and thirty-two households for questionnaire administration in Geographical Open Data Kit (GeoODK) across thirty-six wards in two selected cities of Nigeria. Analytical techniques such as Foster–Greer–Thorbecke indices, correlation, Getis Ord G., and mapping techniques were applied in this study. The results reveal a random spatial pattern of time poverty severity; a negative correlation between income poverty incidence and time poverty incidence; and a positive correlation between income poverty gap and time poverty gap. This study concludes that as many residents escape income poverty, they enter time poverty as they spend more time earning a daily income, which poses a danger in eradicating poverty in all its forms. This study recommends a policy of earning a daily income above the international poverty line without spending more than standard daily working hours if Sustainable Development Goal One is truly achieved.